ASSESSMENT OF ORGANIZATIONAL AND ECONOMIC DETERMINANTS OF INNOVATION AND PRODUCTION EFFICIENCY IN NATIONAL MEAT LIVESTOCK SECTOR - Kushakov, Fakhriddin (International Conference on Business & Management, 2026)
The article analyzes the impact of organizational and economic factors on the innovative development of national beef cattle farming and their role in improving production efficiency. The study examines the production structure of livestock farms, the level of resource utilization, economic performance indicators, and regional characteristics. It also addresses the improvement of innovative approaches and management mechanisms in the development of beef cattle farming. The obtained results contribute to the development of scientifically grounded practical recommendations aimed at improving sector efficiency.